Faktor Yang Berpengaruh Pada Opini Going Concern - Minadi Wijaya; Tjahjani Murdijaningsih (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2019)
The existence of a going concern opinion is an important thing in the auditing report and is of concern to the auditor. In addition to conducting audits with companies by conducting fairness checks on financial statements, giving their opinions on going concern is of concern to the auditor. The company and can be one of the determinants of shareholders to make decisions. This research aims to see several factors, namely auditor quality and company growth as independent variables have a positive influence on the existence of going concern opinion. This study uses the financial statements of LQ45 companies for the period 2012-2016 which are published on the IDX in a row. The researcher used logistic regression as the testing method in this study which resulted that the alternative hypothesis namely auditor quality had a positive effect on acceptable going concern opinion, and the results of the testing of the second hypothesis regarding the growth of the company had a positive effect on the going concern opinion unacceptable.